Chronological changes in baseline disease activity of patients with rheumatoid arthritis who received biologic DMARDs between 2003 and 2012. Issue 3 (May 2015) - Sato, Eri; Tanaka, Eiichi; Ochiai, Moeko; Shimizu, Yoko; Kobayashi, Akiko; Shidara, Kumi; Hoshi, Daisuke; Sugimoto, Naoki; Inoue, Eisuke; Seto, Yohei; Nakajima, Ayako; Taniguchi, Atsuo; et al.
Abstract Background/Purpose. The use of biologic disease-modifying anti-rheumatic drugs (DMARDs) for rheumatoid arthritis (RA) has been increasing since 2003. In this study, we evaluated changes in the characteristics of patients receiving biologic DMARDs daily, in Japan. Methods. The characteristics of all RA patients who received any biologic DMARD at the Institute of Rheumatology, Tokyo Women's Medical University, within 1 year after its approval in Japan, were retrospectively evaluated. The periods of patient enrollment for each biologic agent were: infliximab (IFX), 2003–2004; etanercept (ETN), 2005–2006; tocilizumab (TCZ), 2008–2009; adalimumab (ADA), 2008–2009; abatacept (ABT), 2010–2011; and golimumab (GLM), 2011–2012. We retrospectively collected individual patient characteristics, concomitant medication usage, and disease activity assessed by disease activity score 28 (DAS28) at the time of administration, from the medical records. The retention rate for each agent at 6 months after treatment initiation was also assessed. Results. The numbers of patients who received each biologic DMARD at our institute within 1 year after its approval were: IFX, 49; ETN, 50; TCZ, 62; ADA, 52; ABT, 40; and GLM, 77. From 2003 to 2012, the proportion of patients with prior use of any biologic DMARD increased, as did concomitant use and dose of methotrexate (MTX); however, corticosteroid use and doses decreased. DAS28, at the time of treatment initiation, gradually decreased. At the time of IFX administration, 75% and 25% of patients had high and moderate disease activity respectively, compared to 25% and 58% respectively, of patients who received GLM. No significant difference was observed in the retention rate of biologic DMARDs at 6 months (range, 75.0% to 89.6%). Conclusion. Baseline disease activity of RA patients who received biologic DMARDs between 2003 and 2012 has changed from high to moderate in daily practice in Japan.